Sustitución del colorante sintético rojo No. 40 por colorantes a base de antocianinas usando flor de carbonero rojo y flor de jamaica. (2024)
"One of the most widely used dyes in the food and cosmetics industry is red 40, also known as Allura Red Dye. However, it has raised growing concerns about its adverse effects on consumer health. Recent research has revealed its possible relationship with carcinogenic risks, as well as the ability to cause cognitive problems and obesity in children and adolescents. For this reason, this project seeks to replace it with a safe alternative, such as organic dyes derived from anthocyanins. Anthocyanins are natural pigments present in numerous fruits and vegetables, being the first viable option to replace synthetic pigments. Additionally, they offer health benefits such as antioxidant and anti-inflammatory properties. In this degree work, the possibility of replacing the synthetic dye red 40 with organic dyes obtained from the red coal flower and the hibiscus flower was analyzed, by extracting the anthocyanins present in both plant matrices, carrying out an experiment by means of a solid-liquid extraction in order to evaluate the stability and sensory acceptability of using the organic dye extracted. Additionally, organoleptic tests were carried out to verify the response of the obtained colorant in foods and the feasibility of applying it to the industry was also evaluated by carrying out a scale-up."